Immanuel as die geïnkarneerde tora: Funksionele Jesusbenaminge in die Matteusevangelie as vertelling - Aarde, Andries van (Hervormde teologiese studies, 1987)
Emmanuel as the Torah Incarnate: The names of ]esus in Matthew's storyTwo tendencies in traditional titular Christology are indicated as methodologically and theologically inadequate. Alternatively, the more prominent names of Jesus are discussed as means by which the narrator in Matthew's story characterises Jesus as the fulfiller of the law and the prophets. The Matthaean Jesus can as such be depicted as Emmanuel, the Torah Incarnate. The names dealt with are Teacher, Rabbi, Kyrios, Son of David, Prophet, Messiah, King of the Jews, Son of man and Son of God.